Efektivitas multi drug therapy pada transmisi morbus hansen transplasental - Dhelya Widasmara; Santosa Basuki; Dea Florensia; Ade Setyagraha; Nugrahanti Prasetyorini (DiscoverSys Inc., 2020)
Introduction: The evidence of transplancental transmission of Morbus Hansen (MH) in animal models is a challenge for MH treatment in pregnancy because it brings anxiety for patients and their fetuses. Case: A 31-year-old pregnant woman, first trimester, came with complaints of reddish numbness rash on her hands since 2 years ago. Dermatological examination showed erythematous plaque, multiple, well-defined, irregular borders with hypoaesthesia. There were right and left ulnar nerve enlargement. Acid Fast Bacteria (AFB) from ear lobes and lesion revealed Bacterial Index +2 and Morphological Index 10%. Histopathological examination showed gren zone which indicate MH type BL. Patient was diagnosed with MH Multi Basiler (MB) on G3P2002Ab000 and given MDT MHMB. Postpartum IgM and IgG anti-PGL-1 examination of cord blood and infant blood, also PCR examination of cord blood and amnion showed negative results. Histopathological examination found no AFB on the umbilical cord and placenta. Conclusion: MDT is effective in preventing transplacental transmission of MH from mother to fetus.